Polairud In Overcoming the Crime of Human Smuggling (People Smuggling) in the East Coast Region of North Sumatra - Giri Pratomo; Elvira Fitriyani Pakpahan; Kartina Pakpahan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The aim of the research is to determine the factors that cause people smuggling and their role POLAIRUD in overcoming the crime of human smuggling in the East Coast Region of North Sumatra. The research method uses empirical juridical legal research methods. Empirical legal research in the form of community legal behavior. The data source for empirical legal research is not based on written positive law, but rather the results of observations at the research location. Result Polairud needs to advocate for policies that support increased budgets and resources allocated for operations in water areas. With adequate financial support, Polairud can expand the reach of its operations and increase the effectiveness of law enforcement in strategic but challenging areas such as the east coast of North Sumatra. These suggestions, if implemented well, can help Polairud strengthen its role in protecting Indonesia's territorial waters from the threat of people smuggling and ensure fairer and more effective law enforcement.